2019
DOI: 10.4081/jphia.2019.951
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between water insecurity, hygiene practices, and incidence of diarrhea among children from rural households of the Menoua Division, West Cameroon

Abstract: The objectives of a cross-sectional, semi-quantitative study were to: i) assess the prevalence of water insecurity and its association with water access-related behaviors such as time, distance, and sources of water; ii) identify major themes of concern raised in reference to anxiety, water quality/quantity, and perceived health risk domains of water insecurity, and; iii) examine the relationship between water insecurity, hygiene practices, and diarrhea lincidence among children in rural areas of the Menoua Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 15 publications
4
23
0
Order By: Relevance
“…All three discussions took place in a private setting on different days and were conducted in French by the primary author fluent in the language. The results of previous research conducted in the study area [22,23] and water access-related literature were used to develop the discussion guide. In alignment with the study objectives, the FGD was divided into two sections: (1) water access, its management, and daily water use; and, (2) changes in behavior and strategies used at the household level to manage limited water access.…”
Section: Focus Group Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All three discussions took place in a private setting on different days and were conducted in French by the primary author fluent in the language. The results of previous research conducted in the study area [22,23] and water access-related literature were used to develop the discussion guide. In alignment with the study objectives, the FGD was divided into two sections: (1) water access, its management, and daily water use; and, (2) changes in behavior and strategies used at the household level to manage limited water access.…”
Section: Focus Group Discussionmentioning
confidence: 99%
“…The triangulation strategy was used involving different data collection techniques (FGD vs. KII) and different individuals analyzing the data. The authors also used observations and results of the previous research [22,23] in the study area in order to validate the data of the current study.…”
mentioning
confidence: 98%
“…Based on the findings from previous water access-related studies conducted in the study area [ 25 , 26 ] and existing household water insecurity scales literature [ 6 ], questions for the FGDs were designed.…”
Section: Methodology Of the Data Collectionmentioning
confidence: 99%
“…Hadley and Freeman used a locally tailored scale in Ethiopia and found that each point increase in water insecurity was associated with a 20% increase in the odds of diarrheal prevalence for children under 5 years of age (Hadley & Freeman, 2016). Nounkeu and colleagues used a 6‐item water insecurity scale and found that children in those households classified as water insecure were more likely to report diarrhea than children from water secure households (Nounkeu et al, 2019). Rosinger created a locally appropriate household water insecurity scale in Lowland Bolivia and found that high water insecurity was associated with nine times the odds of diarrhea following a catastrophic flood for adults, but not significantly higher for children, compared to those from low water insecurity households (Rosinger, 2018).…”
Section: Human Biology Implications Of Water Insecuritymentioning
confidence: 99%